Purificação de lacases PPO-I de Botryosphaeria rhodina - Hiroito Obara, Francis Widmann; Varéa-Pereira, Geni; Tomoe Miyagui, Dalva; Corradi Da Silva, Maria de Lourdes [UNESP] (Universidade Estadual de Maringa, 2005)
Laccases are glycoprotein polyphenol oxidases which are involved in fungal pathogenicity and they are also useful for biotechnological applications. The ligninolytic ascomycete, Botryosphaeria rhodina, has been studied as producer of exopolysaccharide and PPO-I and PPO-II laccases induced by veratryl alcohol. However, as the induced laccases have not been isolated, the aim of this study was to purify the enzyme and to identify the carbohydrates constituents of the glycosidic moiety. The fungus was cultivated on broth Vogel, 1% glucose and 30.4mM veratryl alcohol during 4.5 days at 28°C/180 rpm. The extracellular fluid showed high carbohydrate concentration and the stability of PPO-I laccase under conditions of refrigeration and freezing at 4°C-18°C over 40 days. The purification was developed by ultrafiltration using a NMWL 100 and 30 kDa membrane, gelfiltration on Sephadex G-100, and ion-exchange chromatography on DEAE-cellulose. The purified laccase was identified as a glycoprotein, weight molecular 113 kDa, consisting of 40% protein and 60% carbohydrate identified by HPAEC-PAD as fucose, galactose, mannose, glucose and glucosamine.
Purification of laccases PPO-I of fungus Botryosphaeria rhodina
Keywords: Botryosphaeria rhodina; Characterization; Exopolysaccharides; Glycoprotein; Laccase; Purification; exopolysaccharide; fucose; galactose; glucosamine; glucose; glycoprotein; laccase; polyphenol; sephadex; Ascomycetes; biotechnology; enzyme isolation; enzyme purification; enzyme stability; extracellular fluid; fungal virulence; fungus; gel filtration; ion exchange chromatography; nonhuman; ultrafiltration; Ascomycota; Fungi